(untitled) (International Journal of Engineering and Computer Science, 2025)
This article presents approaches for designing scalable AI-CRM systems capable of efficiently processing large volumes of data and delivering real-time analytics. Three primary architectural patterns—microservices, an event-driven architecture with CQRS, and data-processing pipelines—are examined, and their combined use is shown to enhance system flexibility and reliability. The proposed cloud-container infrastructure leverages Docker/Kubernetes, serverless functions, and managed services for queuing, storage, and MLOps, while a service mesh is employed to ensure security and observability. Optimization techniques include in-memory caching, indexing, high-performance model serving on GPU/TPU, comprehensive monitoring with autoscaling, and event streaming. Implementation pathways for the framework are outlined, and its effectiveness is demonstrated through comparison with traditional monolithic, bare-metal solutions. The findings will interest system architects and senior developers in the AI-CRM domain, as well as researchers in distributed computing and machine learning responsible for exploring high-level design patterns (CQRS, Event Sourcing, microservices) and integrating hybrid cloud infrastructures to achieve horizontal scalability. Performance-optimization considerations will also appeal to technical directors of large enterprises seeking to build reliable, adaptive systems for real-time processing of vast customer-data streams.